Effects of Phytoremediation on Microbial Biomass, Composition, and Function in a Sulphide-Rich Tailing From a Metal-Contaminated Region - Nkongolo, K. K.; Spiers, G.; Beckett, P.; Narendrula-Kotha, R. (Frontiers in Environmental Science, 2022)
Mining activities lead to serious land deterioration and large scale mine waste generation. Reclamation has been carried out on several technogenic materials to encourage the development of soils. To date no detailed studies have been conducted to assess if soil developed in reclaimed tailings can be suitable for microbial community sustainability and associated plant population. This study investigated if 1) soil metal contamination affects microbial biomass and composition in sulphite tailings and 2) phytoremediation of tailing increases microbial abundance, diversity, and function. Microbial biomass was assessed using Phospholipid fatty acid analysis (PLFA). Soil bacterial and fungal microbiota was determined by high throughput sequencing of 16S rRNA gene for bacteria and internal transcribed spacer (ITS) region for fungi using the Illumina platform. Total copper, nickel, iron, and titium were higher in unreclaimed sites compared to vegetated areas but the total microbial biomass was significantly higher in reclaimed sites compared to reference areas. More importantly, the levels of microbial biomass were not impacted by metals since the bioavailable Cu, Ni, and Ti were low in all the sites. High bacterial and fungal biomass was associated with elevated organic matter but not with a high pH. Site-specific bacterial and fungal genera were identified. Proteobacteria was the most dominant bacterial phylum while Ascomicota was the predominant fungal phylum. Interestinlgy, Acidiferrobacter, an acidophilic, thermotolerant and facultatively anaerobic was the most predominant genus in unreclaimed site that is characterized by extreme acidity (pH = 2.8). Analysis of microbial diversity revealed higher Chao 1, # of OTUs, Shannon index, and species richness in bacterial and fungal populations from reclaimed sites compared to controls. The levels of β-glucosidase (BG), cellobiohydrolase (CBH), β-N-acetylglucosaminidase (NAGase), aryl sulfatase (AS), acid phosphatase (AP), alkaline phosphatase (AlP), glycine aminopeptidase (GAP), and leucine aminopeptidase (LAP) activities were significantly higher in vegetated sites compared to reference areas. Overall, newly developed soils can sustain diverse microbial communities and associated vegetations.